Co?Doped Stannates ?Reduced Graphene Composites: Effect of Cobalt Substitution on the Electrochemical Sensing of Hydrogen Peroxide - (:unkn) unknown (Elsevier B.V., 2017)
Co−doped stannates, Zn2-xCoxSnO4 (0.5 ≤ x ≤ 1.5), were produced by ceramic synthesis starting from the ZnSnO4 phase. Morphology, structure, and composition of synthesized compounds were examined using scanning electron microscopy, X-ray diffraction analysis (XRD), and X-ray photoelectron spectroscopy (XPS). Using XPS, cobalt ions are shown to have an oxidation state of 2+, and XRD patterns showed the same crystalline structure for all Zn2-xCoxSnO4 (0.5 ≤ x ≤ 1.5) phases, i.e., they are isostructural. The morphology of synthesized compounds shows appreciable differences in particle sizes which range from 80 nm to 500 nm, depending on how the ceramic was synthesized and the cobalt concentration. Co−doped stannates ⁄reduced graphene (rGO) composites were prepared and used to modify glassy carbon electrodes (GCE). The resulting electrodes were evaluated for the amperometric determination of hydrogen peroxide. The catalytic activity of composites towards the oxidation of hydrogen peroxide was highly dependent on quantity of cobalt in the ceramic compound, and also on the quantity of rGO present in the composite. The pure cobalt stannate phase with a ratio of 8:1 (ceramic:rGO) exhibited the best catalytic activity towards hydrogen peroxide oxidation at low potentials (0.400 V). A linear relationship between current and hydrogen peroxide concentration was obtained with a sensitivity of 0.43 μAmM−1 cm−2 and a detection limit of 0.31 μM. © 2017 Elsevier B.V.